The end of a great illusion: Credit crunch and liquidity meltdown - Anastasia Nesvetailova (Danish Institute for International Studies (DIIS), 2008)
This paper argues that the credit crunch is the result of a particular problem in the world financial system, that is, of the phenomenon of 'liquidity illusion.' At the heart of this still poorly under-stood phenomenon lies the spiral of financial innovation and its effects on systemic liquidity. I examine the political-economic mechanisms that had sustained the illusion of liquidity during the boom years, and the mechanisms which contributed to its evaporation during the ongoing crisis. My analysis demonstrates that that while increased investment inflows have been one of the factors behind the North Atlantic credit boom of 2003-2007, the boom - including housing and securitization bubbles - has disguised the fact that the financial system in Anglo Saxon econ-omies has become progressively illiquid. Drawing on the scholarship of Hyman Minsky, I identify three pillars of the liquidity illusion - Ponzi finance; collective thinking by investors; and the credibility function performed by the credit rating agencies - and examine their role in the un-ravelling of the global liquidity illusion.
Keywords: 330; Finanzmarktkrise; Kreditgeschäft; Liquiditätspräferenz; Kapitalmobilität; Internationaler Finanzmarkt; Welt